Economics - McKenzie, Richard B. (Boston : Houghton Mifflin, 1986)
Helps you combine rigorous economic analysis with attention to the issues of economic policy that are alive and important today in this field. This book uses economic terminology when enhancing the analysis so that the reader can build their understanding of global economic developments and evaluate proposals for changes in economic policies.
Includes bibliographical references and index.
aia 04/05/2018
Loans
Keywords: Economics